Predatory cue use in flush responses of a colonial nesting seabird during polar bear foraging. (November 2022) - Barnas, Andrew F.; Geldart, Erica A.; Love, Oliver P.; Jagielski, Patrick M.; Harris, Christopher M.; Gilchrist, H. Grant; Hennin, Holly L.; Richardson, Evan S.; Dey, Cody J.; Semeniuk, Christina A.D.
Abstract : Nest predation is a primary cause of reproductive failure in birds; thus, predators apply strong selective pressure on nesting behaviour, especially risk assessment behaviours during predator encounters at nests. Prey's risk assessments are not static; rather, dynamic risk assessment theory predicts that prey assess risk in real-time and update it according to changes in cues posed by the predator(s). We used drone videography to film nest-flushing behaviours of common eiders, Somateria mollissima, in response to foraging polar bears, Ursus maritimus, on East Bay Island (Nunavut, Canada). We assessed how cue use influenced flushing behaviour and nest fate in a path analysis using 200 observations of 193 eiders in 2017. Our most supported model found that more direct angles of visual gaze and travel angle by polar bears resulted in conspicuous nest flushes by eiders (β = −0.236 ± 0.059), whereas the presence of herring gulls, Larus argentatus, resulted in more discrete flushes of hens walking from their nests (β = −0.181 ± 0.059). Shorter flush initiation distances between eiders and approaching bears resulted in greater nest predation by polar bears (β = −0.203 ± 0.076). We found no support that an eider's visibility from the nest influenced any component of flushing behaviour. We suggest that during encounters with bears, eiders are capable of assessing risk and making appropriate behavioural decisions to reduce the chances of nest loss. However, as the colony experienced heavy predation by bears in 2017, behavioural responses alone appear to be insufficient to mitigate polar bear predation at the population level. Highlights: We examined nesting seabirds' responses to polar bear predation. We used drones to investigate polar bear foraging in a common eider colony. Direct angles of gaze and travel by bears resulted in more conspicuous nest flushes. However, when more gulls were present, eiders' flushes were more inconspicuous.